2020
DOI: 10.5334/gh.853
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean-Style Diet for the Primary and Secondary Prevention of Cardiovascular Disease: A Cochrane Review

Abstract: Background: Diet plays a major role in cardiovascular disease (CVD) risk. Objectives: To determine the effectiveness of a Mediterranean-style diet for the primary and secondary prevention of CVD. Methods: We searched for randomised controlled trials (RCTs) of Mediterranean-style diets in healthy adults and those at increased risk of CVD (primary prevention) and with established CVD (secondary prevention). Results: Thirty RCTs were included, 22 in primary prevention and eight in secondary prevention. Clinical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 59 publications
(198 reference statements)
0
22
0
Order By: Relevance
“…The Mediterranean diet (MD) is typically high in vegetables, fruits, whole grains, beans, nuts, seeds, and olive oil, weekly intake of fish, poultry, eggs, and moderate dairy products, but limits intake of red meat. It is regarded as a healthy and sustainable dietary pattern and is associated with reduced risk factors for cardiovascular disease, 249 and may have protective effects against COVID‐19. As shown in several surveys on changes in eating habits during the pandemic, the adherence to MD increased in some individuals 250–252 .…”
Section: Diet and Lifestylementioning
confidence: 99%
“…The Mediterranean diet (MD) is typically high in vegetables, fruits, whole grains, beans, nuts, seeds, and olive oil, weekly intake of fish, poultry, eggs, and moderate dairy products, but limits intake of red meat. It is regarded as a healthy and sustainable dietary pattern and is associated with reduced risk factors for cardiovascular disease, 249 and may have protective effects against COVID‐19. As shown in several surveys on changes in eating habits during the pandemic, the adherence to MD increased in some individuals 250–252 .…”
Section: Diet and Lifestylementioning
confidence: 99%
“…Like physical activity, eating a heart-healthy diet plays an important role in managing cardiovascular risk. The MeDi has been linked to beneficial effects on hypertension, DM, obesity, and hyperlipidemia [ 170 ]. Additionally, there is evidence that these diets boost cognition and reduce risk of dementia by decreasing vascular inflammation, white matter changes, and Aβ and tau pathology [ 171, 172 ].…”
Section: Promoting Successful Cognitive Agingmentioning
confidence: 99%
“…A Mediterranean dietary pattern has long been associated with a lower incidence of CVD in the general population [6]. Notwithstanding, a recent systematic review and metaanalysis [32] concluded that there is still some uncertainty regarding the effects of a Mediterranean-style diet on CVD and cardiometabolic risk factors for both primary and secondary CVD prevention. Therefore, it is clinically relevant to determine the appropriate degree of adherence in which the aforementioned cardiovascular protection could be reached in pregnant women.…”
Section: Discussionmentioning
confidence: 99%